2016
DOI: 10.1016/j.commatsci.2016.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Computationally implemented modeling of creep of composite materials caused by phase dissolution

Abstract: Multiphasic composites with time-evolving, transient microstructures exhibit time-dependent behavior under load. One mechanism leading to this behavior is the dissolution of loadbearing phases within such materials. When the dissolution process occurs inside one phase of the composite material, the stress transmitted by the dissolving phase transfers into the neighboring phases, resulting in additional deformation of the whole composite. This additional deformation of the macroscopic material manifests as time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…In addition to inherent C‐S‐H viscoelasticity/viscoplasticity, some other mechanisms have also been proposed, including dissolution of load‐bearing phases and poromechanical effects, both of which manifest as time‐dependent transfer of microscale stresses among phases. Recently, a study conducted by Li and Grasley suggested that in unsaturated, early age cement paste, where poromechanical effects can be neglected, the contribution of C‐S‐H viscoelasticity/viscoplasticity to creep/relaxation of cement paste may not be as significant as the creep caused by dissolution of load‐bearing cement grains during the hydration reaction . The gradual dissolution of cement grains induces a redistribution of the stress from dissolving, load‐bearing cement grains to precipitated hydration products, increasing the elastic deformation of the remaining solid constituents, and yielding VE/VP behavior of cement paste on the bulk scale.…”
Section: Introductionmentioning
confidence: 58%
See 4 more Smart Citations
“…In addition to inherent C‐S‐H viscoelasticity/viscoplasticity, some other mechanisms have also been proposed, including dissolution of load‐bearing phases and poromechanical effects, both of which manifest as time‐dependent transfer of microscale stresses among phases. Recently, a study conducted by Li and Grasley suggested that in unsaturated, early age cement paste, where poromechanical effects can be neglected, the contribution of C‐S‐H viscoelasticity/viscoplasticity to creep/relaxation of cement paste may not be as significant as the creep caused by dissolution of load‐bearing cement grains during the hydration reaction . The gradual dissolution of cement grains induces a redistribution of the stress from dissolving, load‐bearing cement grains to precipitated hydration products, increasing the elastic deformation of the remaining solid constituents, and yielding VE/VP behavior of cement paste on the bulk scale.…”
Section: Introductionmentioning
confidence: 58%
“…Its natural configuration, to which the body would return if stimuli were removed, also evolves with time. The kinematic framework of this process is summarized in Figure (for more detail see), where χ's denote the motions of the material body from one configuration to another. For any species i in the composite material, its motion is defined by x i = χ i ( X i , t), where x i is the position vector of species i in the current configuration, X i is the position vector of species i in the reference configuration, and the boldface indicates a vector (or, in general, a higher order tensor).…”
Section: Conceptualizationmentioning
confidence: 99%
See 3 more Smart Citations